The role of different Culex mosquito species in the transmission of West Nile virus and avian malaria parasites in Mediterranean areas. Issue 2 (31st August 2020) - Ferraguti, Martina; Heesterbeek, Hans; Martínez‐de la Puente, Josué; Jiménez‐Clavero, Miguel Ángel; Vázquez, Ana; Ruiz, Santiago; Llorente, Francisco; Roiz, David; Vernooij, Hans; Soriguer, Ramón; Figuerola, Jordi
Abstract: Vector‐borne diseases, especially those transmitted by mosquitoes, have severe impacts on public health and economy. West Nile virus (WNV) and avian malaria parasites of the genus Plasmodium are mosquito‐borne pathogens that may produce severe disease and illness in humans and birds, respectively, and circulate in an endemic form in southern Europe. Here, we used field‐collected data to identify the impact of Culex pipiens, Cx. perexiguus and Cx. modestus, on the circulation of both WNV and Plasmodium in Andalusia (SW Spain) using mathematical modelling of the basic reproduction number ( R 0 ). Models were calibrated with field‐collected data on WNV seroprevalence and Plasmodium infection in wild house sparrows, presence of WNV and Plasmodium in mosquito pools, and mosquito blood‐feeding patterns. This approach allowed us to determine the contribution of each vector species to pathogen amplification. Overall, 0.7% and 29.6% of house sparrows were positive to WNV antibodies and Plasmodium infection, respectively. In addition, the prevalence of Plasmodium was higher in Cx. pipiens (2.0%), followed by Cx. perexiguus (1.8%) and Cx. modestus (0.7%). Three pools of Cx. perexiguus were positive to WVN. Models identified Cx. perexiguus as the most important species contributing to the amplification of WNV in southern Spain. For Plasmodium models, R 0 values were higher when Cx. pipiens was present in the population, either alone or in combination with the other mosquito species. These results suggest that the transmission of these vector‐borne pathogens depends on different Culex species, and consequently, their transmission niches will present different spatial and temporal patterns. For WNV, targeted surveillance and control of Cx. perexiguus populations appear as the most effective measure to reduce WNV amplification. Also, preventing Culex populations near human settlements, or reducing the abundance of these species, are potential strategies to reduce WNV spillover into human populations in southern Spain.